Neonatal vitamin A supplementation improves sheep fertility potential - Li, Yating; Song, Pengkang; Zhao, Jiamin; Zhang, Weipeng; Liu, Xiangdong; Lv, Xiaoyang; Zhao, Junxing (Frontiers in Veterinary Science, 2024)
This study aimed to explore the effects of neonatal vitamin A (VA) supplementation on testis development and spermatogenesis. A total of 32 newborn lambs were intramuscularly injected with corn oil (control group) or corn oil + 2500 IU/kg BW VA (VA group). They were slaughtered and sampled at 3 weeks and 8 months of age to analyze spermatogenesis, cell proliferation, hormone secretion, antioxidant status of the testis, and adult sheep sperm parameters. Compared with the control group, the expression of spermatogonial differentiation-related genes in VA group was up-regulated (P < 0.05). Testis weight, seminiferous tubule diameter, number of spermatogonium and spermatocyte, and sperm density increased significantly in VA group at 8 months of age (P < 0.05). Neonatal VA injection upregulated the expression of the cell proliferation marker PCNA and cell cycle-related genes in the testis (P < 0.05). VA increased the concentrations of testosterone (T), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) in the serum and upregulated steroidogenesis-related genes in the testis (P < 0.05). The antioxidant levels in the VA group were maintained at high levels. The total antioxidant capacity (T-AOC), antioxidant enzyme content and antioxidant-related genes were increased in the testis (P < 0.05). Furthermore, neonatal VA injection activated retinoic acid (RA) signaling to maintain the blood-testosterone barrier (BTB) in the testis of 3-week-old sheep. AMP-activated protein kinase (AMPK) and protein kinase B (AKT) signaling were also modulated in the sheep testis (P < 0.05). Taken together, VA supplementation in newborn rams promotes testis development and spermatogenesis to improve fertility.